Psychiatric nosological historiography - Part I: until the raising and fall of the psychodynamic theory - Gomes, Marleide de Mota (2023)
Introduction: The history of psychiatry encompasses the evolving concepts about the relationship between body and mind and also of the definition of normality, which depend on the knowledge and customs of different times and places. For a better understanding of this journey, this study privileged the presentation of the influential figures on the construction of psychiatric nosology and classifications mainly unfolded on a descriptive or causal basis, from psychics or somatics driving, since the western renaissance. Because of the length of this historical path, this study is divided into two parts. This paper, the first in a two-part series, is a preamble to the development of the new nosography and psychopharmacology of the 21st century, merit of the second paper in this series. Method: Narrative review based on secondary sources. Results: Part One includes a review of prior studies concluding that the psychiatric nosography construction has many stations and it passes through the 18th century more structured morbid classifications based on taxonomies of the natural sciences. Psychiatric classifications navigate the course between different psychiatric theories, often marked by inherent prejudices, alongside advances achieved in neuroscience and its intricate connections with the physiology of emotions, cognition and behaviors, shedding light on their deviations or disorders. This evolution goes in parallel with that of the macro and microanatomy, physiology, chemistry, pharmacology, genetics, internal medicine, mainly neurology, apace with evaluation techniques that also reach the Blood-oxygen-level-dependent imaging (BOLD) fMRI (functional magnetic resonance imaging) that indirectly study the action of neurotransmitters and neuronal signalling. The biologic approach stands in contrast to the psychodynamic theory, particularly dominant until roughly the mid-20th century. Conclusion: The study of psychiatric nosohistoriography helps to understand the conceptual evolution of mental illnesses and the most recent importance of psychopharmacology for this.